Synthesis And Characterization Of Strontium And Cobalt Doped Akermanite Bioceramics - Mohammadi, Hossein (2019)
The akermanite ceramic with the chemical formula (Ca2MgSi2O7) is a calcium (Ca2+), magnesium (Mg2+) containing silicate bioceramics have drawn attentions of biomaterials researchers because they showed more controllable degradation rate and improved mechanical properties compared to phosphate-based bioceramics such as beta-tricalcium phosphate (β–TCP) and hydroxyapatite (HA). In addition, their ionic dissolution products such as Ca2+, Mg2+, silicate (Si4+) have been reported to positively affect the bone cell proliferation and differentiation in vitro and in vivo. However, the low fracture toughness and fracture strength of akermanite limit its biomedical applications, particularly under load-bearing sites. The purpose of this study is to dope strontium (Sr2+) and cobalt (Co2+) into akermanite ceramic to improve their mechanical properties (particularly fracture toughness). This is performed by high energy planetary ball milling of oxide powders of Ca, Mg and Si with Sr and Co (as dopant) for 3 h with speed of 500 rpm. This is followed by sintering in the furnace at 1200°C for 4 h temperature. Sr is bone seeker trace elements which possess positive effects on bone formation (osteogenesis). The Sr concentration of 5, 10 and 15 mol% was chosen in this study. On the other hand, low concentration of Co has effects on vascularization (angiogenesis) and the concentration of 2 mol% and 5 mol% was chosen for Co doping accordingly. In ion doping, the dopant could either partially or fully doped in the host ceramic. Since, partial substitution occurs in in real experimental conditions, the ratio of Sr/Sr+Ca and Co/Co+Mg was chosen. Accordingly, the compositions were categorized as 0.05Sr, 0.10Sr and 0.15Sr based on the Sr/Sr+Ca and 0.02Co and 0.05Co based on Co/Co+Mg ratio. The results obtained confirmed that Sr2+ and Co2+ substitution did not change the silicate structure and akermanite phase. In addition, the Sr2+ and Co2+ substitution enhanced physical and mechanical properties of akermanite. However, the toughness and strength of akermanite were dependent on the Sr2+ (5 mol% optimum) and Co2+ (2 mol% optimum) content. The optimum fracture strength and toughness of Sr-substituted sample was found to be 16.44 and 1.42 MPa.m1/2, respectively. On the other hand, the optimum strength and toughness of Co-substituted sample was 21.35 MPa and 1.68 MPa.m1/2, respectively indicating that Co improves the mechanical properties of akermanite. In vitro bioactivity and biodegradability revealed different apatite morphology depending on the Sr2+ content after 21 days of soaking in SBF solution and controlled the biodegradability of akermanite. Compared to Sr-doped akermanite sample, the Co-doped sample did not show obvious apatite formation and biodegradability after 21 days of soaking in SBF solution compared to pure akermanite. However, the pH value of SBF media showed a higher pH value compared to akermanite possibly due to faster release of Ca2+ into the media. Finally, both akermanite and Sr-substituted akermanite samples showed cytocompatibility while Sr-containing sample showed higher human fetal osteoblast (hFOB) cell viability which demonstrated the positive effect of Sr2+ ions on the hFOB cell proliferation. However, the Co-containing sample showed cytotoxicity on the hFOB cell viability which may indicate the negative effect of Co2+ ions on cell viability.